Modern legislation regarding the challenges of 21st century technology - selected aspects of legal regulations and technology security - Anna Rabajczyk; Monika Wyszomirska; Jacek Zboina (Journal of Modern Science)
This publication discusses legal issues related to selected areas of security, including cybersecurity, digital service security, fire safety as well as safety in the area of nanotechnology – in particular in relation to requirements concerning environmental standards, products and waste management (storage, recycling, incineration, etc.). The authors of the article analyse not only the applicable EU and national regulations, indicating the proposed areas of change, but also discuss the threats related to the use of 21st century technologies and indicate the challenges posed by new technologies in the regulatory area. By analysing extremely different substantive issues covering law, engineering and science, the authors made the same assessment of the relations between law and 21st century technology. The results of research and analyses presented by them concerning both cybersecurity and fire safety and the use of nanotechnology confirm the thesis that law is unable to keep up with the dynamic development of new technologies.